CARDIAC SURGERYThe use of a new hybrid stent graft for the repair of extensive thoracic aortic aneurysms with the frozen elephant trunk method – first Polish experiences - Zembala, Michał; Krasoń, Marcin; Hrapkowicz, Tomasz; Przybylski, Roman; Filipiak, Krzysztof; Borowicz, Marcin; Niklewski, Tomasz; Głowacki, Jan; Wolny, Tomasz; Nadziakiewicz, Paweł; Walas, Ryszard; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
The frozen elephant trunk (FET) technique is a modification of the traditional elephant trunk method, which was introduced by Borst in 1983 in order to treat extensive thoracic aortic aneurysms. The crux of the new method is the different type of aortic prosthesis, consisting of a Dacron part (with or without branches leading to the arterial vessels which exit the aortic arch) and a port for extracorporeal circulation with a self-expanding nitinol stent graft. This combination enables a complete one-stage treatment of the pathologies within the arch and the proximal segment of the descending aorta; moreover, it facilitates the performance of a two-stage hybrid treatment of extensive thoracic aortic aneurysms involving a significant part of the descending aorta. This article presents the cases of four patients with extensive aortic disease, who were implanted with Thoraflex prostheses (Vascutek, Scotland).